Adoptive immunotherapy with autologous T-cell infusions reduces opioid requirements in advanced cancer patients. Issue 1 (January 2020) - Zhou, Xinna; Qiao, Guoliang; Ren, Jun; Wang, Xiaoli; Wang, Shuo; Zhu, Siyu; Yuan, Yanhua; Morse, Michael A.; Hobeika, Amy; Lyerly, Herbert Kim
Abstract : Abstract: Relief of cancer-related pain remains challenging despite the availability of a range of opioid and nonopioid medications. Animal models demonstrate that T lymphocytes may mediate analgesia by producing endogenous opioids, but definitive clinical data are limited. Transfer of ex vivo adoptive cellular therapy (ACT) is being tested as an anticancer therapy. We retrospectively reviewed the medical charts of 357 patients with various malignancies who received 3 intravenous infusions of autologous cytokine-activated T-cell–enriched products. Among these were 55 patients who required opioids for moderate or severe cancer-related pain. Opioid dosage and cancer pain score were recorded daily for 2 consecutive weeks before and 2 weeks after the ACT infusions. The average oral morphine equivalent doses and cancer pain scores were significantly decreased after the ACT infusions. The proportion of patients with breakthrough pain also declined. Moreover, higher frequencies of expanded CD3 +, CD3 + /CD4 +, and CD3 + /CD8 + T cells within the ACT product were associated with favorable analgesic effects. Transient elevations in CD3 + and CD3 + /CD8 + T-cell subpopulations and decreases in CD4 + CD25 + Treg were observed in patients' blood after the ACT. In conclusion, ACT was capable of reducing cancer pain severity and opioid consumption and favorably modulating peripheral blood T-cell populations. Abstract : Adoptive cellular therapy could reduce cancer pain severity, opioid consumption, and improved immune parameters in the management of severe or refractory cancer pain.